Integrated UPLC-MS/MS profiling and network pharmacology-based analysis of the anti-hyperglycemic potential of Baihu Jia Renshen Decoction combined with Sanghuangporus vaninii extract in mice - Jia Zhang; Ying Chen; Yanfa Lin; Zifeng Huang; Xiaodong Ge; Bin Liu; Zirui Huang (Journal of Molecular Histology, 2026)

Impact of extracellular polymeric substances from Skeletonema costatum on the combined toxicity of microplastics and antibiotics in estuarine environment - Jie Lai; Jianhuang Su; Zongling Li; Yan Zheng; Dinglin Hou; Zifeng Zhou; Jiabao Zhu; Bin Lin; Peiyong Guo (Marine Pollution Bulletin, 2026)

Toxic effects of microplastics on extracellular polymeric substances (EPS) in estuarine microalgae under stress conditions - Jianhuang Su; Jiabao Zhu; Dinglin Hou; Yan Zheng; Zongling Li; Bin Lin; Zifeng Zhou; Jie Lai; Peiyong Guo (Environmental Pollution, 2026)

Ecotoxicological risk and environmental assessment of mebendazole: A comprehensive study using freshwater snails as non-target species - Dinghao Li; Ji Wu; Yunyi Hu; Zifeng Zhu; Yao Liao; Yuheng Liu; Yun Huang; Peiying Peng; Du Gao; Zhongdao Wu; Chuan Bai; Xi Sun; et al. (Journal of Hazardous Materials, 2026)

Temperature-dependent transformation of piggery biogas residue pyrolysis products: Balancing resource recovery and environmental safety - Chunyang Chen; Xiujuan Wang; Hongxing Tu; Qianyi Cai; Junshi Tao; Xiaojun Lin; Jingwen Zeng; Jinrong Qiu; Zifeng Luo (Bioresource Technology, 2025)

Electrochemical oxidation of aquaculture wastewater by biogas residue biochar: Effects of chloride and removal of organic pollutants - Xu Pei; Yu Meng; Chengyu Chen; Yongtao Li; Zifeng Luo; Peng Wang; Xiaoqiang Liu; Xueming Lin; Yulong Zhang; Siyi Yang; Zhen Zhang (Biomass and Bioenergy, 2025)

Whether aristolochic acid directly drives hepatocarcinogenesis: comprehensive investigations from mutational signatures to animal models - Lu Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Yanchao Yang; Tong Chu; Dayuan Zheng; Dongfan Yang; Wenzhe Ma (Archives of Toxicology, 2025)

UAVs-UGV cooperative boom sprayer system based on swarm control - Yuli Chen; Zibo Liu; Zifeng Xu; Jianqin Lin; Xianlu Guan; Zhiyan Zhou; Dateng Zheng; Andrew Hewitt (Computers and Electronics in Agriculture, 2025)

Enhanced biodegradation of sulfamethazine in swine manure composting: Pathway elucidation, mechanism insights, and optimization of a novel Bacillus sp. strain - Xiaojun Lin; Jingtong Li; Chunyan Chen; Zifeng Luo; Hongxing Tu; Yuwan Pang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jianfeng Huang; Jingwen Zeng; Jinrong Qiu (International Biodeterioration & Biodegradation, 2025)

Sustainability and challenges of renewable energy in ASEAN countries: Insights from the Indo-Pacific Economic Framework - Chengling Yang; Zifeng Lin; Jiapei Li; Chuangbin Chen (Environmental Development, 2025)

Effects of Astragalus–Ginseng Dietary Supplementation on the Growth and Stress Resistance of Yellow Catfish (Pelteobagrus fulvidraco) - Wenkai Lin; Haijing Xu; Xinlan Ma; Zifeng Yin; Aimin Wang; Junqiang Qiu; Mingyou Li (Fishes, 2025)
Astragalus and ginseng, esteemed as traditional Chinese herbal medicines, have demonstrated the ability to bolster physical health and enhance the immune function of organisms. In this study, the effects of a dietary astragalus–ginseng mixture on the growth performance, intestinal health, and nonspecific immunity of yellow catfish (Pelteobagrus fulvidraco) were evaluated, by measuring growth performance indices, intestinal villus morphology, enzyme activities, and expression levels of immune-related genes. Yellow catfish (n = 120, initial weight: 5.07 ± 0.18 g) were randomly assigned to four dietary groups: a control group (CT, 0 mg/kg) and three astragalus–ginseng treatment groups (AG1, 500 mg/kg; AG2, 1000 mg/kg; AG3, 2000 mg/kg). Each group had three replicates and was fed for six weeks. The results demonstrate that the treatment significantly enhanced the growth performance, as evidenced by increases in FBW, WG, WGR, SGR, and HSI. These improvements may be related to an increase in intestinal villi length and increased LPS activity, both of which are associated with enhanced digestive function. Meanwhile, the activity of antioxidant enzymes in the liver, including CAT, SOD, and GSH, was increased, whereas the level of MDA was decreased. In the serum, GSH was up-regulated, while SOD activity was decreased. Immune-related enzyme activities, such as ALT and LZM, were up-regulated, while AST showed no significant difference. Moreover, the treatment also promoted the expression of the anti-inflammatory factor IL-10. The pro-inflammatory factors, such as IL-1β, IL-6, and TNF-α, were decreased with the addition of low concentrations but increased with high concentrations. In conclusion, supplementation with an astragalus–ginseng mixture could promote growth performance by increasing digestive enzyme activity and intestinal villi length, and improve disease and stress resistance traits by modulating immune genes and antioxidant enzyme activity. A dosage of 1000 mg/kg was found to be optimal.

Response surface methodology and Box-Behnken design optimization of Sulfaquinoxaline removal efficiency and degradation mechanisms by Bacillus sp. strain DLY-11 - Chunyan Chen; Zifeng Luo; Hongxing Tu; Xiaojun Lin; Yuwan Pang; Jianfeng Huang; Jun Zhang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jingwen Zeng; Jinrong Qiu (Journal of Hazardous Materials, 2025)

Bamboo - A potential lignocellulosic biomass for preparation of hard carbon anode used in sodium ion battery - Gengchen Li; Zifeng Hua; Juan Yang; Heshen Hu; Jiefeng Zheng; Xiaojuan Ma; Jiande Lin; Shilin Cao (Biomass and Bioenergy, 2025)

Evaluation of Enrichment Approaches for the Study of the Viromes in Mollusk Species - Tongling Chen; Tiantian Wu; Yunyi Hu; Zifeng Zhu; Ji Wu; Datao Lin; Xi Sun; Zhongdao Wu; Yi-Ping Li (Food and Environmental Virology, 2025)

Species discrimination of Fritillaria Bulbus using PCR-CRISPR/Cas12a-based nucleic acid detection - Dongfan Yang; Yanchao Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Wenzhe Ma (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Nitrogen and phosphorus recovery from livestock wastewater via magnesium ammonium phosphate precipitation: A critical review of methods, progress, and insights - Jingtong Li; Chunyan Chen; Zifeng Luo; Jinrong Qiu; Li Zhao; Jun Zhang; Xue Xiao; Xiaojun Lin; Xiujuan Wang; Qianyi Cai; Jingwen Zeng; Hongxing Tu; et al. (Journal of Water Process Engineering, 2024)

Optimization of degradation conditions for sulfachlorpyridazine by Bacillus sp. DLY-11 and analysis of biodegradation mechanisms - Xiaojun Lin; Jun Zhang; Zifeng Luo; Jingtong Li; Xue Xiao; Xiujuan Wang; Qianyi Cai; Weida Yu; Junshi Tao; Jingwen Zeng; Hongxing Tu; Jinrong Qiu (Journal of Hazardous Materials, 2024)

Anion substitution-induced CuCoSe hollow nanotubes as multifunctional electrode materials for supercapacitors and overall water splitting - Zifeng Zeng; Zhifeng Gao; Zicheng Guo; Xiaowei Xu; Ying Li; Lin Lin; Runping Jia; Sheng Han (Fuel, 2024)

Triclosan-loaded aged microplastics exacerbate oxidative stress and neurotoxicity in Xenopus tropicalis tadpoles via increased bioaccumulation - Dawu Lin; Zifeng Cen; Chaonan Zhang; Xiaojun Lin; Taojie Liang; Yanbin Xu; Li Zheng; Qingxia Qiao; Lu Huang; Kairong Xiong (Science of The Total Environment, 2024)

Invasibility framework to predict the early colonization of alien Sonneratia in mangrove: Implications for coastal area management - Lin Zhang; Zifeng Luo; Xianxian Guo; Yamian Zhang; Yijuan Deng; Mao Wang; Wenqing Wang (Journal of Environmental Management, 2024)

A potential slow-release fertilizer based on biogas residue biochar: Nutrient release patterns and synergistic mechanism for improving soil fertility - Zifeng Luo; Yunliang Li; Xu Pei; Kok Sin Woon; Mengxue Liu; Xueming Lin; Zheng Hu; Yongtao Li; Zhen Zhang (Environmental Research, 2024)

A clustering-based analysis method for simulating seismic damage of buildings in large cities - Xianan Chen; Lingxin Zhang; Xuchuan Lin; Konstantinos A. Skalomenos; Zifeng Chen (Engineering Structures, 2024)

Degradation of sulfonamide antibiotic via UV/MgO2 system: kinetic, application, and mechanism - Yixun Zheng; Zhenjun Xiao; Yijie Lin; Zheng Fang; Deyang Liu; Zifeng Lin; Qianxin Zhang; Ping Chen; Zhenheng Zhang; Lu Xv; Wenying Lv; Guoguang Liu (Environmental Science and Pollution Research, 2024)

Exploring the connection between morphological characteristic of built-up areas and surface heat islands based on MSPA - Jinyao Lin; Keqin Wei; Zifeng Guan (Urban Climate, 2024)

Self-assembly construction of 1D carbon nitride nanotubes and cobalt-modified for superior photocatalytic degradation of sulfonamide antibiotics - Zifeng Lin; Zhongquan Wang; Zihong Xu; Zhenjun Xiao; Zheng Fang; Jin Luo; Ping Li; Ping Chen; Wenying Lv; Guoguang Liu (Chemosphere, 2023)

Enhanced photochemical degradation and transformation of ciprofloxacin in a UV/calcium peroxide system: pH effects, defluorination kinetics, and different components numerical analysis - Zheng Fang; Zifeng Lin; Ping Chen; Mengying Feng; Haijin Liu; Zhenjun Xiao; Zili Lin; Dagaung Li; Dezhu Liu; Yudan Zhang; Wenying Lv; Guoguang Liu (Journal of Cleaner Production, 2023)

Insights into CQDs-doped perylene diimide photocatalysts for the degradation of naproxen - Zheng Fang; Yang Liu; Ping Chen; Daguang Li; Haijin Liu; Zhenjun Xiao; Yixun Zheng; Zifeng Lin; Jin Luo; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2023)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Four first records of trichodinid (Ciliophora: Peritrichia) ectoparasites from cultured molluscs and fishes in China - Zifeng Zhan; Hong Zeng; Nengfeng Lin; Kuidong Xu (Acta Oceanologica Sinica, 2018)

Plasma miR-124 Is a Promising Candidate Biomarker for Human Intracerebral Hemorrhage Stroke - Zifeng Wang; Gang Lu; Johnny Sze; Yao Liu; Sheng Lin; Hong Yao; Ji Zhang; Dan Xie; Quentin Liu; Hsiang-fu Kung; Marie Chia-mi Lin; Wai Sang Poon (Molecular Neurobiology, 2018)

Assessment of the MCC method to estimate sea surface currents in highly turbid coastal waters from GOCI - Zifeng Hu; Delu Pan; Xianqiang He; Dehai Song; Ningli Huang; Yan Bai; Yi Xu; Xiaohua Wang; Lin Zhang; Fang Gong (International Journal of Remote Sensing, 2017)

A method to estimate concentrations of surface-level particulate matter using satellite-based aerosol optical thickness - JinHua Tao; MeiGen Zhang; LiangFu Chen; ZiFeng Wang; Lin Su; Cui Ge; Xiao Han; MingMin Zou (Science China Earth Sciences, 2013)